Knowledge, Attitude, and Food Safety Practices among Street Food Vendors at a Metropolitan District in Ghana: A Cross-sectional Study - Abraham Norman Nortey; Hubert Amu; Ebenezer Senu; Alfred Effah (International Journal of Food Science)
Background. Street food is a vital component of cities and towns in developing countries. However, food poisoning has been associated with inadequate knowledge of food safety practices and inappropriate food handling. We examined the knowledge, attitude, and practices of street food sellers in the Takoradi Submetropolis, Ghana, on food safety and hygienic practice. Method. In this descriptive cross-sectional study, 406 street food vendors were recruited based on a simple random sampling technique from the Sekondi-Takoradi Metropolis, Ghana, using a structured questionnaire. Data collected were analyzed with the chi-square test and binary logistic regression using Stata (version 16) software. Statistical significance was set at p<0.05. Results. The level of knowledge was low among 70.4% of the food vendors, and 51% had negative attitudes towards food safety and hygiene. Food hygiene practices were also poor among 52.3% of the participants. The predictors of low knowledge level were senior high (aOR=0.37, 95% CI (0.19-0.70), p=0.002) and junior high education (aOR=0.52, 95% CI (0.27-0.99), p=0.047). Having senior high education (aOR=0.37, 95% CI (0.17-0.82), p=0.014), prior training on food safety and hygiene (aOR=0.50, 95% CI (0.29-0.84), p=0.010), and having high level of knowledge (aOR=0.33, 95% CI (0.20-0.54), p=0.001) were associated with lower likelihood of negative attitude towards food safety and hygiene. Moreover, having junior high education (aOR=6.20, 95% CI (2.78-13.87), p=0.001), high level of knowledge (aOR=4.70, 95% CI (2.77-7.98), p=0.001), and positive attitude towards food safety and hygiene (aOR=1.76, 95% CI (1.08-2.87), p=0.023) were associated higher odds of good food practice. Conclusion. Knowledge and attitude regarding food safety and hygienic practices was poor among street food vendors. Future initiatives should focus on establishing training programs for food vendors within the metropolitan assembly to improve their knowledge on food safety and hygienic practices.